2014
DOI: 10.1186/1752-1947-8-300
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic pruritus presenting with Hodgkin’s lymphoma: a case report

Abstract: IntroductionParaneoplastic pruritus is defined as pruritus that occurs before or during the natural evolution of a hematologic disease. The reported prevalence is 30% in patients with Hodgkin’s lymphoma. The severity of this pruritus has a very negative impact on patients’ quality of life. Very few studies have been made to examine the efficacy of pharmacological treatments for this type of pruritus. One drug that appears to be effective in this respect is off-label aprepitant, a neurokinin 1 receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Recently, there have been the various successful scientific reports of aprepitant administration for the treatment of refractory pruritus. In these reports, the treatment schedules are not unified, showing 125 mg on day 1, 80 mg on days 3 and 5 [ 6 ]; 125 mg on day 1, 80 mg on days 2–3 [ 4 , 7 ]; 125 mg on day 1, 80 mg on days 2–3, followed by alternating days of 125mg and 80mg thereafter [ 8 ]; 125 mg on day 1, 80 mg on days 2–3, every 2 weeks [ 9 , 10 ]; 80 mg/day [ 5 , 11 , 12 , 13 , 14 , 15 ]; and 80 mg, every 3 days [ 16 ]. Notably, Santini et al have conducted a prospective pilot study for evaluating the efficacy of aprepitant administration in 45 patients, with metastatic solid tumors, treated with EGFR-targeted biological drugs, and with first onset of severe pruritus during the treatment [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been the various successful scientific reports of aprepitant administration for the treatment of refractory pruritus. In these reports, the treatment schedules are not unified, showing 125 mg on day 1, 80 mg on days 3 and 5 [ 6 ]; 125 mg on day 1, 80 mg on days 2–3 [ 4 , 7 ]; 125 mg on day 1, 80 mg on days 2–3, followed by alternating days of 125mg and 80mg thereafter [ 8 ]; 125 mg on day 1, 80 mg on days 2–3, every 2 weeks [ 9 , 10 ]; 80 mg/day [ 5 , 11 , 12 , 13 , 14 , 15 ]; and 80 mg, every 3 days [ 16 ]. Notably, Santini et al have conducted a prospective pilot study for evaluating the efficacy of aprepitant administration in 45 patients, with metastatic solid tumors, treated with EGFR-targeted biological drugs, and with first onset of severe pruritus during the treatment [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, erlotinib was again discontinued, and she was started on aprepitant at 125 mg on day 1 after discontinuation, 80 mg on day 3, and 80 mg on day 5 with the aim of treating the pruritus and skin rush. This treatment schedule for aprepitant administration was decided after studying the various treatment schedules on the basis of the scientific reports of aprepitant administration [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Then, the prompt improvement was observed within 5 days after starting the first dose of aprepitant, leading to a score of 2 for the pruritus on the VAS (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…5 Aprepitant treatment has been used with success for pruritus associated with both malignant and nonmalignant conditions in at least 74 patients, 6 among whom the malignant conditions included cutaneous T-cell lymphoma, Hodgkin lymphoma, and metastatic solid tumors. [5][6][7] Aprepitant has also been used for erlotinib-and nivolumab-induced pruritus in non-small cell lung cancer, which suggests a possible future role for aprepitant in the treatment of pruritus secondary to novel cancer therapies, perhaps including immune checkpoint inhibitors. [8][9][10] However, despite those reports, and likely owing to the multifactorial nature of pruritus, aprepitant is not unviversally effective.…”
Section: Discussionmentioning
confidence: 99%
“…To date, around 80 cases have been published in the literature. [46][47][48][49][50][51][52][53][54][55][56][57][58][59] Its indications serve to treat severe itch in cutaneous lymphomas or pruritus in association with biological oncologic treatments, namely epidermal growth factor receptor tyrosine kinase inhibitor. [47][48][49][50][51][52][53][54][55] Indeed, a pilot study testing aprepitant for 1 week demonstrated an impressive reduction of 8/10 to 0-1 on the VAS in patients with biological cancer treatment-related pruritus.…”
Section: Neurokinin Receptormentioning
confidence: 99%